Developing pH-Modulated Spray Dried Amorphous Solid Dispersion of Candesartan Cilexetil with Enhanced In Vitro and In Vivo Performance - Surendra Poudel; Dong Wuk Kim (MDPI AG, 2021)
Candesartan cilexetil (CC), a prodrug and highly effective antihypertensive agent, is a poorly soluble (BCS Class II) drug with limited bioavailability. Here, we attempted to improve CC's bioavailability by formulating several CC-loaded amorphous solid dispersions with a hydrophilic carrier (PVPK30) and pH modifier (sodium carbonate) using the spray drying technique. Solubility, in vitro dissolution, and moisture content tests were used for screening the optimized formulation. We identified an optimized formulation of CC/PVPK30/SC, which at the ratio of 1:0.5:1 (w/w/w) exhibited a 30,000-fold increase in solubility and a more than 9-fold enhancement in dissolution compared to pure CC. Solid-state characterization revealed that in pH-modulated CC amorphous solid dispersion (CCSDpM), CC's crystallinity was altered to an amorphous state with the absence of undesirable interactions. Stability studies also showed that the optimized formulation was stable with good drug content and drug release under accelerated conditions of up to 4 weeks and real-time stability conditions of up to 12 weeks. Furthermore, pharmacokinetic parameters, such as AUC and Cmax of candesartan, had a 4.45-fold and 7.42-fold improvement, respectively, in CCSDpM-treated rats compared to those in the CC-treated rats. Thus, these results suggest that CCSDpM is highly effective for increasing oral absorption. The application of these techniques can be a viable strategy to improve a drug's bioavailability.